2017
DOI: 10.1002/jcop.21882
|View full text |Cite
|
Sign up to set email alerts
|

What would your neighbor do? An experimental approach to the study of informal social control of intimate partner violence in South Korea

Abstract: Although research on bystander intervention and informal social control of intimate partner violence (IPV) is increasingly common, empirical anomalies remain and experimental studies on population samples are rare. This study reports the effects of a new experimental approach to the study of informal social control of IPV by neighbors on a small population sample of 100 married men in Seoul, South Korea. We hypothesized that men randomly assigned to a high‐perceived informal social control condition would have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Likewise, the findings suggest that informal social control may not be of benefit in primary prevention of physical abuse (preventing parents who have never abused from becoming abusers). However, the significant finding for hypothesis 2 replicates the findings of Emery et al (2017) and does suggest support for the argument that notification of the presence of informal social control can function as an accusation, with the attendant consequences documented in the forensic psychology literature (Bensley et al 2004;Brinke and Porter 2012). When the accusation implicit in informal social control is founded (when the participant has in fact perpetrated child abuse), participants reacted in a way consistent with the predictions of informal social control theory.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Likewise, the findings suggest that informal social control may not be of benefit in primary prevention of physical abuse (preventing parents who have never abused from becoming abusers). However, the significant finding for hypothesis 2 replicates the findings of Emery et al (2017) and does suggest support for the argument that notification of the presence of informal social control can function as an accusation, with the attendant consequences documented in the forensic psychology literature (Bensley et al 2004;Brinke and Porter 2012). When the accusation implicit in informal social control is founded (when the participant has in fact perpetrated child abuse), participants reacted in a way consistent with the predictions of informal social control theory.…”
Section: Discussionsupporting
confidence: 59%
“…Using a random sample of married men from Seoul, South Korea, they manipulated the men's perceptions of the likelihood of informal social control by neighbors, randomly assigning the men to high or low informal social control conditions. Somewhat counter-intuitively, Emery et al (2017) found that although high informal social control appears to have the expected effect for those who have perpetrated family violence in the past year, there is no deterrent effect on self-estimated likelihood of IPV perpetration for the nonperpetrating part of the sample. Using random samples of parents from the populations of Seoul, South Korea and Novosibirsk, Russia, we randomly assigned parents to high or low informal social control conditions.…”
Section: Informal Social Control Of Child Maltreatment: Isc_cmmentioning
confidence: 92%
See 1 more Smart Citation
“…They illuminate how friends may react in today’s climate of domestic violence awareness, demonstrating that ingroup bias may not be as influential as previously thought. Friends of offenders may be in a unique position to recognize their friend’s violence, offer support for behavioral change, and potentially reduce reoccurrence of violent offending (Banyard, 2011; Emery et al, 2016). It is important that friends actively voice disapproval and address IPV behaviors to avoid inferring acceptance and normalization of the violent behavior (McMahon & Banyard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While perpetrators of IPV are unlikely to seek professional help to address their behavior, their close social supports including friends and family may be aware of the situation (Ashley & Foshee, 2005; Emery, Wu, Kim, Pyun, & Chin, 2017). Studies have suggested that informal social control by family members may be a protective factor in reducing severity of IPV, and that perceived neighborhood social control reduces the likelihood that a perpetrator will respond to a relationship problem with violence (Emery et al, 2017; Emery, Yang, Kim, Arenas, & Astray, 2016).…”
mentioning
confidence: 99%